Charge-transfer dynamics of fluorescent dye-sensitized electrodes under applied biases - Godin, Robert (2015)
The development of dye-sensitized solar cells requires an in-depth understanding of the interfacial charge-transfer dynamics that take place between dye sensitizers and semiconductors. Here, we describe a prototype system to probe these dynamics by monitoring in real time the fluorescence of two organic sensitizers, a perylene and a squaraine, bound to a SnO2 semiconductor thin film as a function of potentiostatic control of the Fermi level. The two different sensitizer fluorophores characterized by vastly different redox potentials undergo similar fluorescence modulation with applied bias, an indication that the density of states of the semiconductor largely influences the charge-transfer dynamics while energetics play a minimal role. We further show that the rate of photodegradation of the perylene sensitizer with applied bias provides a suitable marker to study the rate of charge injection and charge recombination. Taken together, our results demonstrate a suitable platform to visualize and study charge-transfer dynamics on films and constitute a step toward achieving single-molecule resolution in our quest to decipher the static and dynamic heterogeneity of charge-transfer dynamics in dye-sensitized photoanodes.